Front Cover. Issue 5 (1st April 2020) - Gislason, Henrik; Collie, Jeremy; MacKenzie, Brian R.; Nielsen, Anders; Borges, Maria de Fatima; Bottari, Teresa; Chaves, Corina; Dolgov, Andrey V.; Dulčić, Jakov; Duplisea, Daniel; Fock, Heino O.; Gascuel, Didier; et al.
Abstract : Cover Image © Svanhildur Egilsdóttir, Marine and Freshwater Research Institute, Iceland. The cover image is based on the Original Article* Species richness in North Atlantic fish: Process concealed by pattern by Henrik Gislason** et al., https://doi.org/10.1111/geb.13068 .***